KEBIJAKAN REDAKSI MEDIA MASSA SUMATERA BARAT DALAM PRAKTIK KONGLOMERASI MEDIA : STUDI KASUS MEDIA ONLINE KLIKPOSITIF.COM DAN KATASUMBAR.COM - Diego Diego; Farah Saniyya; Sarmiati (Jurnal Komunikasi dan Kajian Media, 2025)
The practice of media conglomeration is closely related to the desire of media owners to dominate the market, both the reader market and the advertiser market. This study discusses how the policies and practices of Media Conglomeration are carried out by Classy Corporation which has several business units. The focus of the research is on the online media Klikpositif.com and Katasumbar.com. This research is a qualitative study with a case study approach and a constructivism paradigm. The analysis uses the theory of Political Economy of Media by Vincent Mosco, namely Commodification, Spatialization and Structuration. The results of this study show that the policies of the two online media are oriented towards the advertiser market and the reader market through editorial policies. Both online media utilize Classy Corporation's resources in operating to maximize media management. The commodification of workers in the leaders of the online media Klikpositif.com and Katasumbar.com results in the homogenization of work systems and policies. Keywords: Editorial Policy, Conglomerate, Online Mass Media